Modernity in the domestic architecture of Raul Lino and Ventura Terra at the beginning of the 20th century - Rui Jorge Garcia Ramos (2009)
At the beginning of the 20th century, the domestic architecture of Ventura Terra (1866-1919) and Raul Lino (1878-1974) illustrated their readiness to incorporate new spatial values and new practices into their production of architectural projects. These new aspects, which appeared in different ways in the work of the two architects, showed that their academic training and professional practice had kept them fully apprised of the debate taking place within the discipline at that time, in which one could detect signs of the conflict between a much-desired wish for progress, considered essential for improving the quality of life, and a reaction to change, understood as representing a loss of cultural identity. In this specific case, the works of Terra and Lino can be seen as complementary for an interpretation of modernity, because they shared the same need for reflecting on the legacy of the 19th century and the new ways of creating architecture, leading to the (common) concern with finding (different) answers to the problems of their time. (...)